A review of information technology and national development in third world countries - Yeganegi, Seyed Kamran; MousaZadeh, Nazila (International Journal of Business Management and Entrepreneurship, 2023)
In the new system of globalization, we live in the age of information and media, an age in which information technology and mass media and virtual networks are considered an integral part of the lives of the audience of these technologies. The issue of transfer and absorption of technology in the third world is a complex category that has been around for years, both scientifically and in terms of cultural, political, and economic dimensions, not only in developing countries; Rather, it has occupied many western research societies and international organizations. On the other hand, national development is actually both the key to liberating nations from domination and dependence and the means to establish and consolidate it, because on the one hand, nations cannot stand on their own feet until they are developed, and on the other hand, until they are If they are not on their own feet and do not have a meaningful look inside themselves, they cannot develop, so the purpose of this research is to investigate the role of information technology in the national development of third world countries. In the upcoming review article, we will discuss the effective role that information technologies have on national development. First, we will give definitions of information technology and its types, and then we will examine national development and its dimensions.